Qualidade da água no município de São Mateus : análise parasitológica, microbiológica e físico-química - Nunes, Luiz Gustavo de Paiva (2018)
Water is an essential resource for human life, since 75% of the human body is made up of this element. Considering that the preservation of the quality of this resource is fundamental for the health of the population, the present study sought to evaluate the knowledge of the population about the maintenance of the domestic water reservoirs, besides verifying the quality of the water consumed by the population, mainly the effects of the reservoirs in the physico-chemical, parasitological and microbiological characteristics of water, in the city of São Mateus, northern region of Espírito Santo. The collection of socioeconomic data was done through an interview with the residents. For the microbiological analysis, the substrate technique was used, which allows simultaneous detection and identification of total coliforms and E. coli. A sedimentation method by centrifugation (Blagg method) and a flotation method (Sheather modified) was used for the investigation of parasites. The results were evaluated using descriptive and inferential statistical tools, using Pearson's chi-square test and Poisson's regression analysis. The results showed that all the interviewees were aware of the need to clean the water tank, but in 14.29% (n=10) of the households the cleaning was not performed. Regarding the period of cleaning of the water tank, 61.43% (n=43) of the residents stated that six months was the correct period for their realization, with 55.71% (n=39) of the residents effectively performing the cleaning in that period of time. Through the parasitological analysis of the water, only one hookworm egg was found in a sample from the supply network. The results of the microbiological analysis of the water show that the samples from the domestic reservoirs were more contaminated than those of the public supply network, with a significant difference (p=0.008) between the groups, for contamination by total coliforms. Considering the free residual chlorine content, of the 166 analyzed samples, 94.58% (n=157) had levels below the recommended for disinfection of the water, and in no sample from the domestic reservoir the minimum content was reached. The high degree of microbiological contamination of the two groups may be directly associated to the reduced residual chlorine content of the samples, especially those from the domestic reservoirs. The use of the domestic reservoir had a negative effect on the quality of the water, both in relation to free residual chlorine contents and contamination by total coliforms, which could cause harm to the health of the population.